Biocontrol and plant growth promoting potential of phylogenetically new Streptomyces sp. MR14 of rhizospheric origin - Talwinder Kaur; Riveka Rani; Rajesh Kumari Manhas (AMB Express, 2019)
Abstract The detrimental effects of synthetic fungicides have increased the emphasis for biological control as an effective and safe sustainable alternative method. In the present work, a potent rhizospheric actinobacterium MR14 showed broad spectrum antifungal and plant growth promoting activities indicating the potential to fulfill the need. Phylogenetic analysis confirmed that the isolate could be assigned as new species of the Streptomyces, coded as Streptomyces sp. MR14. It formed clade with Streptomyces daghestanicus but with very low bootstrap value (14%). The MR14 supernatant showed potent antagonistic activity against 13 different tested fungal phytopathogens. The most and least sensitive fungal phytopathogens were found to be Pyricularia oryzae and Fusarium oxysporum with inhibition zones of 31 mm and 11 mm, respectively. The antifungal metabolites produced by strain MR14 were thermostable, photostable, and remained active at extreme acidic and neutral pH. In pot experiments, the Streptomyces sp. MR14 cells, supernatant and extract significantly suppressed Fusarium wilt caused by Fusarium moniliforme in tomato plants. Various growth parameters such as shoot and root lengths, and plant fresh and dry weights were significantly enhanced by 19.65 to 321.62% over the pathogen infested plants only. The treatment with culture cells/supernatant/extract in the rhizosphere soil also reduced the microbial count as compared to control. In addition, the strain also possessed plant growth promoting potential which was indicated by the increase in various agronomic traits from 3.64 to 116.88%. This study provided a scientific validation that the new rhizobacterium Streptomyces sp. MR14 could be further developed as bioformulation, exhibiting biocontrol and plant growth promoting capabilities.